Natural rubber/polystyrene segmented copolymers by gamma radiataion technique: Strutural characteristic studies - Rasit Ali, Roshafima; Mohd. Nor, Hussin; Mohd., Dahlan (2002)
Natural rubber/polystyrene segmented copolymers were synthesized from acrylated liquid natural rubber as the soft segment and styrene monomer as the hard segment with various compositions of hard and soft segments by gamma radiation potvmensauo« Structural f eatures of the segmented copolymers f ormed were characterized by infrared and nuclear magnetic resonance spectroscopy analysis. The existence of absorption bands at 2962, 2928. 2855, 1664, 1450, 1378 and 838 em-I show major characteristics of natural rubber in the segmented copolymer. Peaks at 30'8 and 3024 em" indicated the existence of benzene aromatic ring. The absorption bands at 29/9 and 2848 cm,t show the asymmetry and symmetry stretching of -CHI 'for potystyrere The 'n and He NMR spectra a/so exhibit al/ the fe atures of aery/ated liquid natural rubber as the soft segment and polystyrene as the hard segment indicating that the copolymers made up ofthe two segments.